2022
DOI: 10.5897/jpbcs2021.0986
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity assessment among 18 elite cashew tree genotypes (Anacardium occidentale L) selected in Western Burkina Faso

Abstract: The development of cashew orchards increased in recent years in Burkina Faso, due to high nut demand on international markets. However, little activities have been oriented toward cashew cultivar development, and farmers often use seed plants with little or no information about genetic characteristics of the material at hand. Therefore, a description of cashew diversity is needed to provide guidance to farmers and identify elite material for the crop improvement. In this study, phenotypic attributes of cashew … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
(57 reference statements)
2
0
0
Order By: Relevance
“…The existence of substantial overall genetic diversity and two distinct genetic population groupings in East Timor point to multiple introductions comprising different founder populations. These results are in accordance with a recent report in Burkina Faso that suggests several historical cashew introductions with well-performing cashew cultivars disseminated through the same route across producing areas ( Moumouni et al, 2022 ). If the introduction occurred as a one-time event, the founder effect would have been reflected with a low genetic diversity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The existence of substantial overall genetic diversity and two distinct genetic population groupings in East Timor point to multiple introductions comprising different founder populations. These results are in accordance with a recent report in Burkina Faso that suggests several historical cashew introductions with well-performing cashew cultivars disseminated through the same route across producing areas ( Moumouni et al, 2022 ). If the introduction occurred as a one-time event, the founder effect would have been reflected with a low genetic diversity.…”
Section: Discussionsupporting
confidence: 93%
“…In Cô te d’Ivoire, cashew genetic diversity was studied using SSRs and the resultsnrevealed an overall heterozygosity deficit and a high intra-population genetic diversity among the screened cashew populations ( Kouakou et al, 2020 ), which is in accordance with the AMOVA results of this study where the most genetic diversity was depicted within populations. The results obtained from this study also agree with a recent study from Burkina Faso, where a substantial amount of genetic diversity was observed across the 18 cashew accessions screened with four SSRs ( Moumouni et al, 2022 ).…”
Section: Discussionsupporting
confidence: 91%